Creating a diagnostic test to assess conceptual understanding of fraction operations - Juwita, Dia Prima; T, Ahmad Yani; Yundari, Yundari (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Fraction operations are fundamental in mathematics education, yet many students face challenges in mastering these concepts. Effective assessment tools are crucial for identifying areas of difficulty and guiding instructional improvements.Aim: This study aims to develop a diagnostic test to accurately measure the conceptual understanding of fraction operations among students in the Elementary School Teacher Education Program (PGSD) at STKIP Melawi.Method: Utilizing a research and development approach with mixed methods, this study follows Ebel's Model of Test Development. The process includes item selection, validation, and reliability testing, involving both qualitative and quantitative analyses.Results: The developed diagnostic test demonstrated strong validity and reliability metrics. Analysis revealed that students commonly struggle with both the conceptual and procedural aspects of fraction operations. Frequent errors were noted in the interpretation and execution of solution steps. No student achieved the highest possible score, indicating significant gaps in understanding. The N-Gain analysis showed an average score of 0.5610, suggesting medium to high effectiveness in identifying learning challenges, with individual scores ranging from 0.32 to 0.93.Conclusion: The diagnostic test developed in this study provides a robust tool for assessing the conceptual understanding of fraction operations. It highlights specific areas where students encounter difficulties, offering valuable insights for targeted instructional strategies. Integrating this diagnostic test into the curriculum can enhance the ability to diagnose and address learning obstacles, ultimately improving mathematics education outcomes.